Effectiveness of Prophylactic Ephedrine vs Fluid Preload in Prevention of Hypotension in Spinal Anesthesia for C-Section - Muhammad Saadat Ali, Raheela Shaheen, Zainab Fareed, Muhammad Azeem Mir, Zulqarnain Qureshi, Jawad Ahmad Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypotension following spinal block can be reduced or minimized prophylactically left lateral uterine displacement, volume loading with crystalloid solutions, phenylephrine infusion or ephedrine administration. Fluid pre loading does not negate the hypotension entirely but decreases the risk. This however is time consuming and vasopressors are often required to correct associated hypotension. Prophylactic ephedrine administration lowers the risk of hypotension at the expense of reactive hypertension if spinal block fails and subsequent conversion to general anesthesia. Aim: To compare the efficacy of prophylactic use of ephedrine versus fluid (Hartmann’s solution) preload in women undergoing cesarean section under spinal anesthesia at a teaching hospital. Study design: Randomized controlled trial. Place and duration of study: Department of Anesthesiology, Nishtar Hospital Multan, from 1st March 2020 to 30th September 2020. Methodology: A total of 100 women, twenty to forty years of age undergoing cesarean section were included. Patients with known hypertension, eclampsia, bleeding diathesis, injection site infection, deformity of spinal column or patients having valvular heart diseases were excluded. Group A women were given prophylactic ephedrine while Group B were given fluid (Hartmann’s solution) preload. After induction of spinal anesthesia continuous blood pressure monitoring was done for fifteen minutes to diagnose hypotension. Hypotension was noted and recorded by the researcher. Results: The mean age of women in group A was 28.04±6.07 years and in group B was 28.26±6.13 years. Majority of the patients, 56, were between twenty to thirty years of age. The mean BMI in group A was 29.06±3.37kg/m2 and in group B was 29.38±3.50 kg/m2. Efficacy of prophylactic use of ephedrine to prevent hypotension was observed in 37(74%) patients and in 25(50%) patients in fluid preload group undergoing cesarean sections under spinal anesthesia. Conclusion: The frequency of hypotension is lower in parturient undergoing spinal anesthesia with prophylactic use of ephedrine as compared to women having fluid (Hartmann’s solution) preload. Keywords: Spinal anesthesia, Hypotension, Ephedrine